2002
DOI: 10.1103/physrevb.66.104503
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional crossover and hidden incommensurability in Josephson junction arrays of periodically repeated Sierpinski gaskets

Abstract: We report a study of overdamped Josephson junction arrays with the geometry of periodically repeated Sierpinski gaskets. These model superconductors share essential geometrical features with truly random (percolative) systems. When exposed to a perpendicular magnetic field B, their euclidian or fractal behavior depends on the relation between the intervortex distance (imposed by B) and the size of a constituent gasket, and was explored with high-resolution measurements of the sample magnetoinductance L(B). In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…It is also worth mentioning the recently observed geometric quantization (Sergeenkov and Araujo-Moreira 2004) and flux induced oscillations of heat capacity (Bourgeois et al 2005) in artificially prepared JJAs as well as recently predicted flux driven temperature oscillations of thermal expansion coefficient (Sergeenkov et al 2007) both in JJs and JJAs. At the same time, successful adaptation of the so-called two-coil mutual-inductance technique to impedance measurements in JJAs provided a high-precision tool for investigation of the numerous magnetoinductance (MI) related effects in Josephson networks (Martinoli and Leeman 2000, Meyer et al 2002, Korshunov 2003, Tesei et al 2006. To give just a few recent examples, suffice it to mention the MI measurements (Meyer et al 2002) on periodically repeated Sierpinski gaskets which have clearly demonstrated the appearance of fractal and Euclidean regimes for non-integer values of the frustration parameter, and theoretical predictions (Korshunov 2003) regarding a field-dependent correction to the sheet inductance of the proximity JJA with frozen vortex diffusion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also worth mentioning the recently observed geometric quantization (Sergeenkov and Araujo-Moreira 2004) and flux induced oscillations of heat capacity (Bourgeois et al 2005) in artificially prepared JJAs as well as recently predicted flux driven temperature oscillations of thermal expansion coefficient (Sergeenkov et al 2007) both in JJs and JJAs. At the same time, successful adaptation of the so-called two-coil mutual-inductance technique to impedance measurements in JJAs provided a high-precision tool for investigation of the numerous magnetoinductance (MI) related effects in Josephson networks (Martinoli and Leeman 2000, Meyer et al 2002, Korshunov 2003, Tesei et al 2006. To give just a few recent examples, suffice it to mention the MI measurements (Meyer et al 2002) on periodically repeated Sierpinski gaskets which have clearly demonstrated the appearance of fractal and Euclidean regimes for non-integer values of the frustration parameter, and theoretical predictions (Korshunov 2003) regarding a field-dependent correction to the sheet inductance of the proximity JJA with frozen vortex diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, successful adaptation of the so-called two-coil mutual-inductance technique to impedance measurements in JJAs provided a high-precision tool for investigation of the numerous magnetoinductance (MI) related effects in Josephson networks (Martinoli and Leeman 2000, Meyer et al 2002, Korshunov 2003, Tesei et al 2006. To give just a few recent examples, suffice it to mention the MI measurements (Meyer et al 2002) on periodically repeated Sierpinski gaskets which have clearly demonstrated the appearance of fractal and Euclidean regimes for non-integer values of the frustration parameter, and theoretical predictions (Korshunov 2003) regarding a field-dependent correction to the sheet inductance of the proximity JJA with frozen vortex diffusion. Besides, recently (Tesei et al 2006) AC magnetoimpedance measurements performed on proximity-effect coupled JJA on a dice lattice revealed unconventional behaviour resulting from the interplay between the frustration f created by the applied magnetic field and the particular geometry of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a careful analysis of Eq. (2) reveals that the observed resonance occurs for x ffi x r ðIÞ, where x = 40 kHz is the frequency of the applied AC current I AC ðtÞ ¼ I sin xt and x r ðIÞ ¼ 2 p À Á xLxI U 0 is the current induced resonance frequency with L x ¼ L 1þx 2 s 2 being the dynamical inductance of the plaquette [2,17,18].…”
Section: Discussionmentioning
confidence: 93%
“…These localized states become delocalized in the presence of a magnetic field 3 . Owing to such distinctive properties, SPG structures have been studied extensively over the years in many contexts, and several other unique features have been observed [4][5][6][7][8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%